Ferner: Berner - Krempel, Ulrich; Kunstmuseum Bern (Bern : Kunstmuseum Bern, 1989)
Hanswalter, Graf ; Kronenberg, Christian ; Marjanov, Wasa
Ferner: Berner / Bernois, d'ailleurs, Weisser Saal Kunstmuseum Bern, 7. März bis 30. April 1989
boek